Research on multi-stage strategy of low carbon building material’s production by small and medium-sized manufacturers: A three-party evolutionary game analysis - Xu, Qiang; Liu, Yuyang; Chen, Chen; Lou, Falin (Frontiers in Environmental Science, 2023)
Using green technology by building materials manufacturers to produce low-carbon building materials is an effective way to control carbon emissions and promote traditional industries' green and low-carbon development. Based on the government, small and medium-sized building materials manufacturers, and scientific research institutes, this paper sets 15 variables that affect the strategy selection of game participants, establishes an evolutionary game model under the constraint of the carbon tax, explores the behavioral strategies of the three parties in the industry life cycle to produce low-carbon building materials, and analyzes the sensitivity of critical factors. Results: The government plays a leading role in the initial stage, which is gradually replaced by the market-leading mechanism as the low-carbon building materials industry develops to maturity. The government's decision-making behavior is almost unaffected by the two, and appropriate subsidies and carbon tax penalties at each stage of the industry life cycle can help improve the enthusiasm of the other two parties to participate in low-carbon behavior. Establishing a reasonable income distribution coefficient between small and medium-sized building materials manufacturers and scientific research institutes is more conducive to speeding up the stable state than transferring and selling technology.